Quark beam function at next-to-next-to-next-to-leading order in perturbative QCD in the generalized large- Nc approximation - Behring, A; Melnikov, K; Rietkerk, R; Tancredi, L; Wever, C (American Physical Society, 2019)
We present the matching coefficient for the quark beam function at next-to-next-to-next-to-leading order in perturbative QCD in the generalized large Nc-approximation, Nc ∼ Nf ≫ 1. Although several refinements are still needed to make this result interesting for phenomenological applications, our computation shows that a fully-differential description of simple color singlet production processes at a hadron collider at N3LO in perturbative QCD is within reach.